-Analisis Indikasi Kecurangan Laporan Keuangan Menggunakan Model Beneish M-Score pada Perusahaan Property dan Real Estate - Septian, Defel; Khairunnisa; Rivan Gunawan (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This research aims to predict, analyze and identify fraudulent financial reports using the Benish M-Score method. The data collection method in this research is documentation. The sample used in this research is 35 Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2019 - 2022. The data analysis technique uses descriptive statistical analysis using the benchmark ratio index method. Based on the results of this research, it shows that the DSRI parameter index is classified as 24% manipulator, 14% gray company, and 62% non-manipulator. GMI is classified as a manipulator 33%, gray company 15%, and non-manipulator 52%. AQI is classified as a manipulator 14%, gray company 26%, and non-manipulator 60%. SGI is classified as a manipulator 13%, gray company 19%, and non-manipulator 70%. SGAI is classified as a manipulator 48%, gray company 1%, and non-manipulator 51%. LVGI is classified as a manipulator 14%, gray company 19%, and non-manipulator 67%. TATA is classified as a manipulator at 19%, a gray company at 6% and a non-manipulator at 75%. Companies classified as manipulators based on the 7 (seven) parameter indices are 31%, gray companies 2%, and non-manipulators 67%. Further research should not only focus on one sector but rather use two different business line sectors so that it can produce more comprehensive conclusions.